Technological university in Brazil: examining the development and (de)construction of the model (International Journal of Scientific Research and Management (IJSRM), 2021)
Based primarily on an analysis of laws and legal frameworks, this qualitative exploratory study aims to examine the development, context, construction, as well as deconstruction, of the technological university model in Brazil. The Federal University of Technology – Paraná (UTFPR) is the only technological university in the country. The analysis presented herein demonstrates that its development is the outcome of movements and efforts within its predecessor, the Federal Center of Technological Education of Paraná (CEFET-PR), to respond to the deconstruction of the technical education model, on which the Institution was based, during the Fernando Henrique Cardoso government. The concept of a technological university has not been replicated in any government since the transformation of CEFET-PR to UTFPR, not even during the Workers’ Party (PT) government, which introduced the model. We conclude that, despite efforts from within, the legal apparatus and the pursuit of certain characteristics and goals, such as obtaining world class status, are aligning UTFPR increasingly toward the profile of traditional universities.